Search and Rescue Applications: On the Need to Improve Ocean Observing Data Systems in Offshore or Remote Locations - Futch, Victoria; Allen, Arthur (Frontiers in Marine Science, 2019)
Search and rescue (SAR) in remote maritime locations is a difficult mission. One of the limitations in these isolated regions is the low density of available oceanographic data for model validation. In order to examine the state of remote search and rescue a review of maritime search theory and advances was conducted. This included basic drift theory, leeway, available environmental data, and the current methods used by the United States Coast Guard for SAR operations. In particular the U.S. Coast Guard’s fourteenth district’s SAR case history was examined and it was found that 60% of SAR cases fall outside of areas that have high-resolution wind and current data, with only global scale model forecasts available. In addition, 2% of cases occurred in offshore waters ( > 12nm from land) and exceeded 36 hours in asset response time. Three SAR simulations were run off the coast of Oahu, Hawaii using the same wind data, but different surface current models. These simulations had extremely large (up to 12,000 km2) search areas, highlighting the need for solutions that narrow these expected areas.